Management of Atypical Slipped Capital Femoral Epiphysis : Current Concept Review - Lindgren, Amelia M.; Lieber, Alexander M.; Shah, Suken A.; Thacker, Mihir M. (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Atypical slipped capital femoral epiphyseal (SCFE) is associated with endocrine or metabolic disorders and radiation therapy. In this review, we discuss the clinical presentation for endocrinopathies, such as hyperparathyroidism, hypothyroidism, and growth hormone deficiency as well as renal osteodystrophy, radiation-induced, and valgus SCFE, with pertinent case examples. Routine laboratory screening of all patients with SCFE is likely not cost-effective. Patients with atypical SCFE are often short in stature, underweight, and present either older or younger than the typical age range (10-16 years old) of idiopathic SCFE. Patient’s fitting these criteria should undergo an endocrine workup. While uncommon, prompt recognition of atypical SCFE is crucial as coordinated care with pediatric subspecialists is necessary. In situ fixation with cannulated screws is the most common fixation method and bilateral fixation is recommended.